The iron trial - Black, Holly; Clare, Cassandra (Black, Holly. Magisterium, 2014)
Warned away from magic all of his life, Callum endeavors to fail the trials that would admit him to the Magisterium only to be drawn into its ranks against his will and forced to confront dark elements from his past.